Complement in renal transplantation: The road to translation. (September 2017) - Jager, Neeltina M.; Poppelaars, Felix; Daha, Mohamed R.; Seelen, Marc A.
Highlights: Complement is already activated in the donor and negatively impacts renal graft outcome. Complement production during preservation can be used as a marker for post-transplant renal function. Complement inhibition during ischemia-reperfusion reduces renal inflammation and apoptosis. Complement-targeted therapeutics could be a possible treatment in rejection. Abstract: Renal transplantation is the treatment of choice for patients with end-stage renal disease. The vital role of the complement system in renal transplantation is widely recognized. This review discusses the role of complement in the different phases of renal transplantation: in the donor, during preservation, in reperfusion and at the time of rejection. Here we examine the current literature to determine the importance of both local and systemic complement production and how complement activation contributes to the pathogenesis of renal transplant injury. In addition, we dissect the complement pathways involved in the different phases of renal transplantation. We also review the therapeutic strategies that have been tested to inhibit complement during the kidney transplantation. Several clinical trials are currently underway to evaluate the therapeutic potential of complement inhibition for the treatment of brain death-induced renal injury, renal ischemia-reperfusion injury and acute rejection. We conclude that it is expected that in the near future, complement-targeted therapeutics will be used clinically in renal transplantation. This will hopefully result in improved renal graft function and increased graft survival.